2010
DOI: 10.4102/jsava.v81i1.90
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of changes over time in serum creatine kinase activity and C-reactive protein concentration in dogs undergoing hemilaminectomy or ovariohysterectomy

Abstract: The extent of trauma in a patient can be difficult for a clinician to quantify. A prospective study was performed on 2 groups of dogs undergoing either ovariohysterectomy or hemilaminectomy. The serum activity of creatine kinase and serum concentration of C-reactive protein were evaluated preoperatively and then at 4, 6, 8, 12, 24 and 48 hours postoperatively in both groups. The results were compared statistically both within and between the 2 groups. A wide range of results was found at each time point for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
(48 reference statements)
4
19
0
Order By: Relevance
“…31 In another study, serum CK activity was measured over 48 hours after HL and OVH. 32 Similar to our study, clear stratification in serum CK activity was observed according to the type of surgery. In that study, serum CK activity after HL did not return to baseline at 48 hours.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…31 In another study, serum CK activity was measured over 48 hours after HL and OVH. 32 Similar to our study, clear stratification in serum CK activity was observed according to the type of surgery. In that study, serum CK activity after HL did not return to baseline at 48 hours.…”
Section: Discussionsupporting
confidence: 89%
“…This assumption is based on a single pharmacokinetic study in which the supernatants of dog muscle homogenates were injected IV and IM into 6 dogs . In another study, serum CK activity was measured over 48 hours after HL and OVH . Similar to our study, clear stratification in serum CK activity was observed according to the type of surgery.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…CK and AST have been measured in serum of dogs as a marker of muscle damage under different conditions, such as hemilaminectomy or ovariohysterectomy [16], exercise [10], and after anesthesia [17]. However, to the authors’ knowledge no studies about CK and AST in saliva in dogs have been published previously.…”
Section: Introductionmentioning
confidence: 99%
“…37 Increases in plasma CK activity in dogs are associated with cell-membrane leakage and therefore will be evident in any condition associated with muscular inflammation, necrosis, or degeneration. 38,39 Creatine kinase has a half-life of only 2 to 3 hours. 40 Thus, high serum CK activity is indicative of recent and active muscle injury.…”
Section: Discussionmentioning
confidence: 99%